Analysis of Difficulties of Junior High School Students in Solving Closed and Open Mathematical Problems - Anggraeni, Rina; Juandi, Dadang; Usdiyana, Dian (International Journal of Ethno-Sciences and Education Research, 2022)
This study aims to describe the difficulties of junior high school students in solving closed and open mathematical problems and to describe the causes of junior high school students experiencing these difficulties. As many as 25 students of class VIII-D from one of the State Junior High Schools in Bandung Regency were used as research samples. Data was collected by using test techniques, interviews, and document studies. The stages of data analysis carried out are data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that students had difficulty in converting the problem into a mathematical model, determining the required decision variables, calculating multiplication and division operations, and determining more than one answer in solving open problems. The difficulties experienced by these students are caused by the following: students feel that the problem given is something new, students are less careful in understanding the problems given, students still do not master the material, students are less careful in performing arithmetic operations, and students not accustomed to solving problems in the form of problem solving and open questions.